Evaluation of the Specificities of Five DNA Amplification Methods for the Detection of Neisseria gonorrhoeae - Palmer, H. M. (American Society for Microbiology, 2003)
The intragenus specificities of five molecular diagnostic methods for Neisseria gonorrhoeae were determined. Three assays were considered suboptimal. Molecular detection of N. gonorrhoeae from sites where other Neisseria spp. commonly occur or from any site in low-prevalence settings should be confirmed by a test targeting a different genetic locus.